Communities’ awareness on environmental and social impacts of stone quarrying and its associated factors in Farta Woreda, Northwest, Ethiopia - Mulugeta Asmamaw Mebratu; Mulugeta Birhan Nurie; Kinde Gebeyehu Reta; Tigabu Desie Emiru (Journal of Degraded and Mining Lands Management, 2021)
Stone quarrying has a considerable impact on land, water, air, natural resources, and social welfare. The objective of this study was to assess communities’ awareness of the environmental and social impacts of stone quarrying in Farta woreda, Northwest Ethiopia.  The study used a cross-sectional research design. The 359 sample respondents were randomly selected. Both quantitative and qualitative data were collected using household surveys, interviews, focus group discussions, and field observation methods. A binary logistic regression model was done to identify the independent variables of communities unaware of the impacts of stone quarrying. 62.7% and 57.38% of the surveyed households had aware of the impacts of stone quarrying social and environmental, respectively. Age of households heads from 31 - 40 (AOR = 1.272, 95% CI = (0.598-2.708), from 41 -50 age (AOR = 2.152, 95% CI = (0.947- 4.889), from 51- 65 age (AOR = 3.207, 95% CI = (1.405-7.321), Educational level of household heads, elementary school (1-8) (AOR = 2.985, 95% CI = (1.523-5.852), secondary school and above (AOR = 3.794, 95%  CI = (1.841-7.820),  Income of household heads from 10000 to 20000 birr (AOR = 2.254, 95% CI = (1.236 - 4.109), Income less than 1000 birr (AOR = 2.493, 95% CI = (1.419 - 4.380) were associated with unaware community on the impact of stone quarry. To solve present and future environmental and social problems, the study woreda Environmental Protection Offices should enhance communities’ awareness through awareness creation and environmental education program.